Observation of very high dielectric constant in Sr(Fe1-xAlx)0.5Nb0.5O3 ceramics prepared by molten salt technique - Thanatep Phatungthane (2018)
© 2015 Elsevier Ltd and Techna Group S.r.l. All rights reserved. Sr(Fe < inf > 1-x < /inf > Al < inf > x < /inf > ) < inf > 0.5 < /inf > Nb < inf > 0.5 < /inf > O < inf > 3 < /inf > (xâ‰ & 0.20) powders were synthesized via the molten-sals process. Pure phase perovskite was obtained at a relatively low calcination temperature of 800 °C. The Sr(Fe;bsubesubbsubesubbsubesubbsubesubbsubesub & ceramics exhibited pure phase perovskite for x < 0.20 ceramics. Dielectric measurements indicated that all ceramics showed a strong dielectric frequency dispersion, especially for the x=0.05 ceramic. Very high dielectric constants (ε > 199,000 for temperatures > 200 °C) were observed for the x=0.05 ceramics. Al doping enhanced the dielectric temperature stability and reduced the loss tangent. Impedance spectroscopic analysis indicated that the dielectric behaviour of the ceramics could be related to the Maxwell-Wagner polarization mechanism, since the ceramics exhibited heterogeneous conduction.